Clinical manifestations and treatment outcomes in HIV-1-infected children receiving antiretroviral therapy in Karachi, Pakistan - Fatima Mir; Farah Naz Qamar; Naila Baig-Ansari; Azra Ghayas Abro; Syed Qamar Abbas; Mohammed Ahmed Kazi; Arjumand Rizvi; Anita Kaniz Mehdi Zaidi (Journal of Infection in Developing Countries)
Introduction: The impact of antiretroviral (ARV) therapy on immunological and growth parameters in HIV-positive children in Pakistan has not been reported to date. Methodology: A retrospective chart review of children diagnosed with HIV at the Sindh AIDS Control Proigramme (SACP) and registered at the Aga Khan University, Karachi, between January 2005 and 2013 was conducted, evaluating clinical and laboratory profiles of HIV+ ARV+ children for ARV impact (serial height and weight CD4 and viral counts). Results: Twenty-four children were diagnosed and registered as HIV positive over five years, and 20 were started on ARV. Six were excluded from analysis (ARV duration < 6 months). Nine (64.3%) of 14 fulfilled WHO criteria for treatment failure at a median duration of 25 weeks (IQR 18-32) on ARV and underwent resistance genotyping. All nine had NNRTI resistance, two had high-grade NRTI resistance (≥ 4 thymidine analog mutations). Median age at start of ARV was 71.5 weeks (IQR 37.5-119). Median baseline weight for age (WAZ) and height for age (HAZ) z-scores changed from -1.94 to 1.69 and -1.99 to -1.59, respectively, after six months of therapy. Median CD4 percentage and viral load at baseline changed from 13.8 to 17.8, while viral load changed from 285 × 104 copies to zero at six months. Conclusions: ARV improved absolute CD4 and viral counts. Weight and height did not  improve significantly, highlighting the need for aggressive nutritional rehabilitation. Early development of ARV resistance in these children requires formal assessment.